Can recentivism become a horizon of fulfilment of infinitely-valued logic? - Bańka, Józef (Folia Philosophica, 2012)
The author of the paper starts with reminding that recentivism (Latin: recens - actual) might be summarised in a claim that the depiction of certain event, although possible at all times, is true only at the present time. At the same time, the author explains that each act of existence is always a discovery of that existence. Seen along such lines, recentivism is a limitative idea taking some of the characteristics (such as being true or existence) as not reserved to some forms of time such as past and future. The author refers to Jan Łukasiewicz, who claimed that to understand future as “not ready yet” it is necessary to ascribe third value to propositions concerning future. Łukasiewicz also claimed that choice will be made between two-valued and infinitely-valued logic. With reference to this remark the author claims that Łukasiewicz’s infinitely-valued logic may be fulfilled in the horizon set by the recentivist ontology, which addresses every moment of “now” into “never ready” future. Hence, according to recentivism, to grasp the future as “never ready” n-value needs to be ascribed to propositions concerning future, that is, choice needs to be done in favour of infinitely-valued logic.